Palaku’s Position in the Traditional Marriage of the Dayak Muslim Community in Tewah District, Gunung Mas Regency - Kusuma, M Prayoga Hadi (Jurnal Indonesia Sosial Sains, 2024)
The Dayak Muslim community in Tewah District, Gunung Mas Regency is sometimes quite burdensome for some men with the high value of the act (maskawin) so that the prospective groom is not able to fulfil it, even though this behaviour is chosen by the Tewah community as a legal foothold in the marriage tradition. This research aims to focus on the position of the perpetrators in the customary marriage of the Muslim Dayak community in Tewah District, Gunung Mas Regency, the amount of the perpetrators in the customary marriage of the Muslim Dayak community in Tewah District, Gunung Mas Regency and the perpetrators in customary marriage in Tewah District, Gunung Mas Regency are determined in the form of land. This research includes empirical research with the type of legal sociology. It is studied through a socio-legal qualitative approach which is analyzed through the theory of Legal Certainty. The results of this research are: the position of the perpetrator in the Dayak customary marriage is first, the position of the perpetrator as a dowry, second, the position of the perpetrator as a condition, third, the position of the perpetrator as a symbol of self-esteem. The implications of these findings are the need for a balance between traditional values and the economic ability of the prospective groom, as well as dialogue to adapt customary practices to current socio-economic conditions. This study demonstrates the importance of flexibility and adaptation in traditional practices to reduce excessive financial burden on individuals.